Cruise Crimes: Economic-Legal Issues and Current Debates - Thomas R Panko; Babu P George; Tony L Henthorne (Amfiteatru Economic Journal, 2009)
Cruise tourism is one of the sunshine sectors of international tourism and is growing rapidly in many parts of the world. It is estimated that the growth rate of cruise tourism is twice the rate of tourism overall. Notwithstanding all the positives that accompany this growth, many critics have drawn attention to the “dark side” of cruise crimes. The eco-system aboard the cruise ship offers a fertile ground for the occurrence of crimes. The present paper examines the issue of crimes onboard from multiple standpoints and suggests some remedial measures that would lead to better management of cruise crimes. A presentation of the recent initiatives by the U.S. legislative bodies aimed at containing cruise crimes is also provided.
Keywords: K42; 330; cruise ships; criminology aboard; cruise crime typology; crime prevention; industry initiative; legislative intervention; and USA